Peranan Guru Geografi untuk Meningkatkan Kedisiplinan dan Tingkat Kesedaran Peserta Didik di SMPN 10 Kayu Putih Kota Ambon - Aufat, Sartila; Leuwol, Ferdinand Salomo; Manakane, Susan Evelin (Universitas Pattimura, 2026)
Current educational challenges lie not only in academic aspects but also in character development, particularly in student discipline and environmental-social awareness. This study aims to analyze the role of geography teachers in improving student discipline and awareness at SMPN 10 Kayu Putih. A descriptive qualitative method was employed, using data collection techniques such as observation, interviews, documentation, and field notes. The findings reveal that geography teachers play a vital role in shaping student behavior through contextual learning and direct experiences integrated with values of natural and social order. These integrated values encourage students to internalize discipline as a necessity, not a mere obligation. This research highlights the broader dimension of geography learning in character formation. The implication is that teachers need to be empowered through contextual and reflective training.